A method for preparing high-toughness and high-conductivity PIPD-reinforced graphene fiber
By introducing PIPD into graphene fibers and using wet spinning technology and ion cross-linking treatment, the problem of insufficient mechanics and conductivity of graphene fibers is solved, and high toughness and high conductivity are achieved, which is suitable for a variety of high-performance applications.
Patent Information
- Application Number
- CN202411597566.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-11
AI Technical Summary
In the prior art, graphene fibers have limitations in terms of mechanical properties and electrical conductivity, especially when interlayer fractures are prone to occur under mechanical loads, resulting in material failure. At the same time, the interface performance between the graphene sheet layer and the polymer matrix is insufficient, which affects the overall performance of the material.
High toughness and high conductivity PIPD-reinforced graphene fibers were prepared by mixing graphene oxide (GO) solution with PIPD solution. PIPD contains hydroxyl groups and aromatic heterocycles, which can form hydrogen bonds and π-π interactions with GO, improving the mechanical and electrical conductivity of the fiber. The metal ions in the solidification bath are ionically crosslinked with PIPD/GO, further improving the stability and performance of the fiber.
The fibers have a combination of high toughness and high conductivity, and the fibers have significantly improved elongation, ultimate tensile strength and fracture toughness, and the conductivity has also reached a high level. This method can be applied in the fields of bulletproof fabrics, bulletproof armor plates, flexible supercapacitor electrodes, wearable electronic textiles and fiber motors.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of graphene oxide fibers and relates to a method for preparing a PIPD-reinforced graphene fiber with high toughness and high conductivity. Background Art
[0002] Two-dimensional graphene sheets have high electrical conductivity, high thermal conductivity and unique optical properties. Assembling two-dimensional sheets into macro structures through molding processes can be used in fields such as energy storage, electronic devices, composite materials, sensors, biomedicine, and aerospace. In the field of energy storage, graphene-based supercapacitors and lithium-ion batteries have attracted widespread attention due to their excellent electrical conductivity and high surface area. They can improve the charge and discharge rate and energy density of energy storage devices. In the field of sensors, graphene's high surface area and sensitive electronic properties make it an ideal material for detecting various chemicals and biomarkers. In the field of biomedicine, graphene is used to manufacture drug delivery platforms, biomarkers, and electrode materials due to its good biocompatibility and conductivity. In the field of aerospace, the light weight and high strength of graphene make it particularly valuable in lightweight components and protective coatings. Graphene films and graphene fibers are the two main macroscopic structures. Although graphene films and graphene fibers have outstanding electronic and mechanical properties, their performance in applications is still limited to a certain extent. In particular, since graphene sheets are stacked together only by van der Waals forces, this weak interaction force may cause fractures between sheets when mechanical loads are applied, thereby increasing the risk of material failure. The alignment and high orientation of graphene sheets in the fiber are crucial to the mechanical properties of the final fiber, and new methods need to be explored to improve the alignment and orientation between sheets to maximize the mechanical, electrical and thermal conductivity of the fiber. In addition, the interfacial properties between graphene sheets and other materials (such as polymer matrices) will affect the performance of the final product. Enhancing the interaction between graphene sheets and improving the interfacial forces between them and the matrix are the key to improving the overall performance of the material. The weak adhesion between graphene sheets and polymer matrix materials affects the mechanical properties and structural integrity, and is very likely to cause stress concentration or stress release under peak stress, resulting in performance degradation that is inconsistent with the expected performance. Therefore, when designing graphene fibers for reinforcing composites, special attention should be paid to how to improve the interfacial interaction between sheets and improve the compatibility of graphene with matrix materials.
[0003] The strategies to improve the mechanical properties of graphene fibers in existing studies mainly include metal ion cross-linking reinforcement, organic molecules, polymers and two-dimensional material reinforcement. The existing technology mostly utilizes polymer-modified graphene to prepare graphene fibers. The polymers used mainly include polyvinyl alcohol (such as patents CN202211190776.5 and CN202211161902.4), chitosan-modified boron nitride (such as patent CN202310211329.1) and silk fibroin (such as the document Silk fibroin reinforced graphene fibers with outstanding electrical conductivity and mechanical strength), etc. Other polymers include polyacrylonitrile (PAN), polymer lignin, polyether sulfone (PES), polysulfone (PS), polyethylene (PE), polylactic acid (PLA), polyphenylene ether (PPO), polyimide (PI), polyacrylic acid (PAA), polyepoxy resin, polyurethane (PU), polyvinylidene fluoride (PVDF), polylactic acid-lactide (PLLA) and polymethyl methacrylate (PMMA), etc. The addition amount of the above polymers is more than 2wt%.
[0004] Specifically, patent CN202311526717.5 discloses a polyacrylonitrile / graphene composite fiber with a core-sheath structure. When the mass fraction of polyacrylonitrile reaches 8.5 wt%, the graphene fiber has a higher strength (500 MPa) and conductivity (770 S·cm -1 Patent CN202211175033.0 discloses a method for preparing high-performance graphene fibers, wherein modified graphene oxide, polyacrylic acid and polyamide are mixed in a mass ratio of 2:1:2, and hydrogen bonding is used to make them have high strength (100 MPa) and conductivity (373 S·cm -1 ). Reference 1 (Matter, 2022, 5(12): 4437-4449.) Ultra-strong graphene oxide-based fibers reinforced by crystalline-amorphous superstructures have high strength. The addition of 37.2 wt% ZrO 2 With 8.5wt% PVA, the toughness reaches up to 10.6 MJ / m 3 Reference 2 (Carbon, 2023, 203: 886-894.) mentioned that after adding 2wt% silk fibroin, the graphene composite fiber has excellent mechanical strength and toughness of 16.1 MJ / m 3 , the conductivity is 2.7×10 5 S·m -1Reference 3 (Nano Letters, 2024, 24(14): 4256-4264.) Adding 50 wt% of polyvinyl alcohol and polyethylene oxide, the interlayer entanglement is regulated by hydrogen bonds and ionic bonds to improve the toughness, and the toughness is as high as 52 MJ / m 3 .
[0005] In the above-mentioned method of adding polymers for toughening and strengthening, on the one hand, due to the high amount of polymer added, although the mechanical properties of the reduced graphene fiber are improved, the conductivity is greatly reduced. In the technology of adding a small amount of polymer, it is mainly the hydrogen bonds and π-π interactions between the polymer and graphene oxide that make the composite fiber have the effect of strengthening and toughening, but the hydrogen bonding force is the main force. This type of interaction is greatly weakened after the graphene oxide is reduced to graphene due to the reduction of oxygen-containing functional groups, thus resulting in more pores in the fiber after reduction and reduced toughness.
[0006] Therefore, it is of great significance to study a method for preparing PIPD-reinforced graphene fibers with high toughness and high conductivity to solve the problems existing in the prior art. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing PIPD-reinforced graphene fibers with high toughness and high conductivity.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing high-toughness and high-conductivity PIPD (poly 2,5-dihydroxy-1,4-phenylene pyridinium diimidazole) reinforced graphene fiber, comprising mixing a graphene oxide (GO) solution with a PIPD solution to prepare a spinning solution, using two coagulation baths to perform wet spinning, and then sequentially performing chemical reduction and vacuum drying after spinning to obtain high-toughness and high-conductivity PIPD reinforced graphene fiber;
[0010] The solvents of both graphene oxide solution and PIPD solution are methanesulfonic acid; the methanesulfonic acid solvent environment can promote the structural orientation and crystallization of PIPD while maintaining the lamellar structure of graphene oxide, and promote the interfacial interaction (hydrogen bonds and other polar interactions) between PIPD and GO, thereby improving the mechanical properties of graphene composite fibers.
[0011] The content of PIPD in the spinning solution is 0.1~50wt% of graphene oxide;
[0012] The first coagulation bath is a metal ion / phosphoric acid aqueous solution. Phosphoric acid slows down the solute solvent exchange, and ion cross-linking enhances the fiber strength. The second coagulation bath is an ethanol / water mixed solution to wash away the residual metal ions.
[0013] In the first coagulation bath, the metal ion concentration is 2-5 wt%, and the phosphoric acid concentration is 2-20 wt%. In the second coagulation bath, the mass percentage of ethanol relative to water is 60-90%.
[0014] The metal ion is Ca 2+ Mg 2+ 、Co 2+ , Fe 3+ 、Al 3+ or Cr 3+ ;
[0015] The spinning solution solvent is methanesulfonic acid. Due to the large molecular weight of methanesulfonic acid, the double diffusion rate in the coagulation bath is slow. Under the condition of only water as the coagulation bath, an obvious skin-core structure will be formed, which will reduce the mechanical properties. Therefore, it is necessary to control the precipitation rate of the solvent in the coagulation bath, from the slow diffusion of the first channel to the fast diffusion of the second channel, so that the structural uniformity inside and outside the fiber is increased, thereby improving the mechanical properties to a certain extent;
[0016] The high-toughness and high-conductivity PIPD-reinforced graphene fibers have an elongation at break of 2-20%, an ultimate tensile strength of 250-1500 MPa, and a fracture toughness of 10-70 MJ / m 3 , the conductivity is 10 2 ~10 6 S·m -1 .
[0017] As the preferred technical solution:
[0018] According to the method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber as described above, the content of PIPD in the spinning solution is 0.1-1wt% of the graphene oxide, the elongation at break of the high-toughness and high-conductivity PIPD-enhanced graphene fiber is 2-10%, and the fracture toughness is 10-30 MJ / m 3 , the conductivity is 5×10 5 ~10 6 S·m -1 .
[0019] According to the method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber as described above, the content of PIPD in the spinning solution is 1-15wt% of the graphene oxide, the elongation at break of the high-toughness and high-conductivity PIPD-enhanced graphene fiber is 5-15%, and the fracture toughness is 30-40 MJ / m 3 , the conductivity is 10 4 ~5×10 5 S·m -1 .
[0020] According to the method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber as described above, the content of PIPD in the spinning solution is 15-30wt% of the graphene oxide, the elongation at break of the high-toughness and high-conductivity PIPD-enhanced graphene fiber is 15-18%, and the fracture toughness is 40-50 MJ / m 3 , the conductivity is 10 3 ~10 4 S·m -1 .
[0021] According to the method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber as described above, the content of PIPD in the spinning solution is 30-50wt% of the graphene oxide, the elongation at break of the high-toughness and high-conductivity PIPD-enhanced graphene fiber is 18-20%, and the fracture toughness is 50-70 MJ / m 3 , the conductivity is 10 2 ~10 3 S·m -1 .
[0022] The method for preparing a high-toughness and high-conductivity PIPD-reinforced graphene fiber as described in any of the above items, the specific preparation steps are as follows:
[0023] (1) Pre-treating the graphene oxide powder: dispersing the graphene oxide powder in deionized water, filtering and freeze-drying to obtain a graphene oxide powder with a few layers (less than 20 layers);
[0024] (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 24 to 72 h, and ultrasonicating for 1 to 3 h during the stirring process to prepare a graphene oxide solution with a concentration of 0.1 to 2 wt%;
[0025] (3) Add PIPD fibers (PIPD fibers prepared by laboratory wet spinning have a diameter of 30-100 μm, a thermal decomposition temperature greater than 520 °C, and a primary fiber tensile strength greater than 1 GPa) into methanesulfonic acid and stir for 24-72 h. Ultrasonication is performed for 1-3 h during stirring to prepare a PIPD solution with a concentration of 0.1-1 wt%;
[0026] (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, and performing wet spinning;
[0027] (5) After chemical reduction of the fiber obtained by spinning in step (4), the fiber is taken out and repeatedly washed with ethanol until the iodine ions are completely washed out, and then vacuum dried to obtain high-toughness and high-conductivity PIPD-enhanced graphene fiber.
[0028] The method for preparing a high-toughness and high-conductivity PIPD-reinforced graphene fiber as described above comprises the following steps: in step (1), graphene oxide powder is dispersed in deionized water, specifically, the graphene oxide powder is stirred in deionized water for 48 to 96 hours, and ultrasonication is performed for 2 to 3 hours during the stirring process;
[0029] Use 300~600 mesh nylon cloth for filtration.
[0030] In the method for preparing the high-toughness and high-conductivity PIPD-enhanced graphene fiber as described above, the spinning speed in step (4) is 5-20 mm·min -1 , the collection rate is 5~20 mm·min -1 , and is continuously collected during the spinning process. After spinning, it is placed in a 40~60 ℃ oven to dry and remove the solvent.
[0031] In the method for preparing a high-toughness and high-conductivity PIPD-reinforced graphene fiber as described above, the reducing agent used for chemical reduction in step (5) is a hydroiodic acid / ethanol mixture, the volume ratio of hydroiodic acid to ethanol is 1:0.1-3, and the hydroiodic acid is a 45% by mass aqueous solution of hydrogen iodide.
[0032] Principle of the invention:
[0033] The present invention prepares a high-toughness and high-conductivity graphene fiber by adding high-molecular polymer PIPD for modification through wet spinning. The hydroxyl groups contained in PIPD are easy to combine with graphene oxide to form hydrogen bonds, which increases the flexibility of PIPD / GO fibers. In addition, PIPD contains a large number of aromatic heterocycles (phenylene pyridine groups and benzene rings), which have the advantages of high rigidity and stability. It can form strong hydrogen bonds, multiple π-π interactions and van der Waals interactions with GO sheets, which is not only conducive to the formation of uniform and stable spinning solution, but also the strong interface interaction between the two after molding greatly improves the performance of the composite fiber. After wet spinning, PIPD / graphene oxide fibers formed a dual-phase crystal structure. The reasons for the formation of the dual-phase crystal are: 1) Heterogeneous nucleation: GO sheets act as nucleating agents, inducing PIPD molecular chains to arrange and crystallize in an orderly manner on their surface, thereby forming microcrystalline regions; 2) Formation of synergistic structure: The strong hydrogen bonding between GO will form a liquid crystal structure, while the PIPD molecular chains have a rigid, highly ordered structure. When PIPD and GO are mixed, the PIPD molecular chains tend to be arranged in parallel on the surface of the GO sheets to maximize π-π stacking and hydrogen bonding interactions; 3) Mechanical stretching orientation-induced crystallization: The stress during spinning and stretching induces further orientation and crystallization of the PIPD molecular chains and GO sheets, and PIPD microcrystalline regions are evenly distributed around the GO crystal regions; and PIPD, which is far away from the GO crystal regions, acts as a bridge between the crystal regions due to its longer molecular chain. During the stretching process, the presence of dual-phase crystal regions and amorphous regions can promote stress dispersion, increase ductility and plastic deformation capacity, and absorb a large amount of energy and passivate crack tips. Due to the formation of the dual-phase crystal structure, the fracture toughness and conductivity are improved, and the metal ions contained in the coagulation bath can be ionically cross-linked with the PIPD / graphene oxide nanosheets, making the system more stable and further improving the mechanical properties of the graphene oxide fibers.
[0034] After GO reduction, although the reduction of GO oxygen-containing functional groups leads to the weakening of hydrogen bonding with PIPD, the partial π-π conjugated structure is restored, the π electron delocalization area increases, and the multiple π-π interactions between PIPD and graphene are further enhanced, so that PIPD / graphene fibers still maintain excellent flexibility and conductivity. In addition, the rigid molecular chain and large molecular weight of PIPD provide a larger contact area, which matches the rigid large sheet structure of RGO or graphene. Therefore, the non-covalent interactions before and after reduction are stronger than those of other polymers.
[0035] Beneficial effects:
[0036] (1) The present invention provides a method for preparing a high-toughness and high-conductivity PIPD-reinforced graphene fiber, which is modified by using a high molecular polymer PIPD. The hydroxyl groups contained in PIPD are easy to combine with graphene oxide to form hydrogen bonds, and there are π-π interactions and van der Waals forces between layers. Only a small amount of PIPD is needed to form PIPD / graphene oxide fibers, which increases the strength, flexibility and conductivity of PIPD / graphene oxide fibers. It is expected to be applied to bulletproof fabrics, bulletproof armor plates, flexible supercapacitor electrodes, wearable electronic textiles and fiber motors.
[0037] (2) The method for preparing a high-toughness and high-conductivity PIPD-reinforced graphene fiber of the present invention improves the fracture toughness and conductivity due to the formation of a dual-phase crystal structure, and the metal ions contained in the coagulation bath can be ionically cross-linked with the PIPD / graphene oxide nanosheets, making the system more stable, thereby further improving the mechanical properties of the graphene oxide fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 XRD spectra of PIPD, 7.5%PIPD / GOFs and 50%PIPD / GOFs; wherein, 7.5%PIPD / GOFs means that the content of PIPD in the spinning solution during preparation is 75% of graphene oxide; 50%PIPD / GOFs means that the content of PIPD in the spinning solution during preparation is 50% of graphene oxide;
[0039] Figure 2 for the multiple strong non-covalent interactions between PIPD and graphene oxide;
[0040] Figure 3 It is the orientation process of the dual-phase crystal region in the spinning nozzle;
[0041] Figure 4 This is a SEM image of the high-toughness and high-conductivity PIPD-reinforced graphene fiber prepared in Example 3;
[0042] Among them, 1- graphene oxide liquid crystal, 2- PIPD microcrystals, 3- methanesulfonic acid, 4- metal ions. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0044] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0045] Conductivity: The conductivity of the fiber was measured by a four-probe conductivity tester.
[0046] Mechanical properties: The elongation at break and ultimate tensile force of the fiber were tested by a tensile-compression dynamometer (model: American Mark-10 IntelliMESUR 2.3.1). The fiber diameter was tested by a scanning electron microscope (model: Hitachi High-Tech Field Emission Scanning Electron Microscope SU8230), and then the fiber cross-sectional area was calculated, and then the tensile strength and fracture toughness were calculated.
[0047] Example 1
[0048] A method for preparing high-toughness and high-conductivity PIPD-enhanced graphene fiber, the specific preparation steps are as follows:
[0049] (1) Pretreatment of graphene oxide powder: stirring the graphene oxide powder in deionized water at 800 rpm for 48 h, ultrasonicating for 2 h during stirring, and then filtering with 300 mesh nylon cloth. After precooling at -18 °C for 24 h, freeze-drying for 24 h to obtain a few-layer graphene oxide powder.
[0050] Among them, the mass volume ratio of graphene oxide powder to deionized water is 1 g:20 mL;
[0051] (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 48 h, and ultrasonicating for 2 h during the stirring process to prepare a graphene oxide solution with a concentration of 1 wt%;
[0052] (3) PIPD fibers (diameter 30-100 μm, thermal decomposition temperature 530 °C, primary fiber tensile strength 1.2 GPa) were added to methanesulfonic acid and stirred for 24 h. Ultrasonication was performed for 2 h during stirring to prepare a PIPD solution with a concentration of 1 wt%;
[0053] (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, using two coagulation baths to perform wet spinning, and drying in an oven at 40°C after spinning;
[0054] The content of PIPD in the spinning solution is 15 wt% of graphene oxide; the first coagulation bath is FeCl 3 / phosphoric acid aqueous solution, FeCl 3 The concentration of 3 wt% and the concentration of phosphoric acid was 10 wt%; the second coagulation bath was an ethanol / water mixed solution with a volume ratio of ethanol to water of 3:1; the inner diameter of the needle was 0.4 mm, and the spinning speed was 10 mm min -1, the collection rate is 10 mm·min -1 ;
[0055] The biaxial crystal orientation process in the spinning nozzle results in Figure 3 As shown, graphene oxide liquid crystal 1 and PIPD microcrystal 2 are uniformly dispersed in methanesulfonic acid 3 solvent. After the extrusion process through the narrow channel of the spinning needle, the arrangement of the liquid crystal and the microcrystal is more orderly. After reaching the spinning needle port, the metal ions 4 participate in cross-linking graphene oxide and PIPD, strengthening the connection between the sheet and the polymer chain, achieving the effect of strengthening and toughening. During the extrusion process in the confined space of the spinning hole, the two crystal regions induce each other to align in an orderly manner.
[0056] (5) The fibers spun in step (4) were chemically reduced at 60°C for 24 h using 20 mL of a 1:3 hydroiodic acid / ethanol mixture, and then vacuum dried at 80°C for 36 h to obtain high-toughness and high-conductivity PIPD-reinforced graphene fibers; the hydroiodic acid was a 45% by mass aqueous solution of hydrogen iodide.
[0057] The resulting high-toughness and high-conductivity PIPD-reinforced graphene fiber has an elongation at break of 15%, an ultimate tensile strength of 800 MPa, and a fracture toughness of 39.7 MJ / m 3 , the conductivity is 10 4 S·m -1 .
[0058] like Figure 2 As shown, the left and right sides are the structural formulas of PIPD and graphene oxide sheets, respectively, and the middle is the strong hydrogen bonds, multiple π-π interactions and van der Waals interface forces formed between the two. The rich and stable interface interactions between the two are conducive to the enhancement of fiber performance after spinning and molding.
[0059] Example 2
[0060] A method for preparing high-toughness and high-conductivity PIPD-enhanced graphene fiber, the specific preparation steps are as follows:
[0061] (1) Pretreatment of graphene oxide powder: stirring the graphene oxide powder in deionized water at 700 rpm for 48 h, ultrasonicating for 2 h during stirring, and then filtering with 300 mesh nylon cloth. After precooling at -18 °C for 24 h, freeze-drying for 24 h to obtain a few-layer graphene oxide powder.
[0062] The mass volume ratio of graphene oxide powder to deionized water is 1 g:20 ml;
[0063] (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 24 h, and ultrasonicating for 2 h during the stirring process to prepare a graphene oxide solution with a concentration of 1 wt%;
[0064] (3) PIPD fibers (diameter 30-100 μm, thermal decomposition temperature 530 °C, primary fiber tensile strength 1.2 GPa) were added to methanesulfonic acid and stirred for 24 h. Ultrasonic treatment was performed for 1 h during stirring to prepare a 0.1 wt% PIPD solution.
[0065] (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, using two coagulation baths to perform wet spinning, and drying in an oven at 40° C. after spinning;
[0066] The content of PIPD in the spinning solution is 0.1 wt% of graphene oxide; the first coagulation bath is MgCl 2 / phosphoric acid aqueous solution, MgCl 2 The concentration is 2 wt%, and the phosphoric acid concentration is 2 wt%; the second coagulation bath is an ethanol / water mixed solution with a volume ratio of ethanol to water of 3:1; the inner diameter of the needle is 0.5 mm, and the spinning speed is 5 mm·min -1 , the collection rate is 5 mm·min -1 ;
[0067] (5) The fibers spun in step (4) were chemically reduced at 60 °C for 24 h using 20 mL of a 1:0.1 volume ratio of hydroiodic acid / ethanol mixture, and then vacuum dried at 60 °C for 24 h to obtain high-toughness and high-conductivity PIPD-reinforced graphene fibers; the hydroiodic acid was a 45% by mass aqueous solution of hydrogen iodide.
[0068] The resulting high-toughness and high-conductivity PIPD-reinforced graphene fiber has an elongation at break of 2%, an ultimate tensile strength of 250 MPa, and a fracture toughness of 10.3 MJ / m 3 , the conductivity is 10 6 S·m -1 .
[0069] Example 3
[0070] A method for preparing high-toughness and high-conductivity PIPD-enhanced graphene fiber, the specific preparation steps are as follows:
[0071] (1) Pretreatment of graphene oxide powder: stirring the graphene oxide powder in deionized water at 700 rpm for 72 h, ultrasonicating for 3 h during stirring, and then filtering with 600 mesh nylon cloth. After precooling at -18 °C for 24 h, freeze-drying for 48 h to obtain a few-layer graphene oxide powder.
[0072] The mass volume ratio of graphene oxide powder to deionized water is 1 g:40 ml;
[0073] (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 36 h, and ultrasonicating for 2 h during the stirring process to prepare a graphene oxide solution with a concentration of 0.1 wt%;
[0074] (3) PIPD fibers (diameter 30-100 μm, thermal decomposition temperature 530 °C, primary fiber tensile strength 1.2 GPa) were added to methanesulfonic acid and stirred for 72 h. Ultrasonic treatment was performed for 1.5 h during stirring to prepare a 0.5 wt% PIPD solution.
[0075] (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, using two coagulation baths to perform wet spinning, and drying in an oven at 50° C. after spinning;
[0076] The content of PIPD in the spinning solution is 1 wt% of graphene oxide; the first coagulation bath is CoCl 2 / phosphoric acid aqueous solution, CoCl 2 The concentration is 2 wt%, and the phosphoric acid concentration is 5 wt%; the second coagulation bath is an ethanol / water mixed solution with a volume ratio of ethanol to water of 3:1; the inner diameter of the needle is 0.4 mm, and the spinning speed is 5 mm·min -1 , the collection rate is 5 mm·min -1 ;
[0077] (5) The fibers spun in step (4) were chemically reduced at 90 °C for 12 h using 20 mL of a 1:1 hydroiodic acid / ethanol mixture, and then vacuum dried at 70 °C for 30 h to obtain high-toughness and high-conductivity PIPD-reinforced graphene fibers; the hydroiodic acid was a 45% by mass aqueous solution of hydrogen iodide.
[0078] like Figure 4 As shown in the figure, after wet spinning, the PIPD / graphene oxide fiber formed a dual-phase crystal structure; the final high-toughness and high-conductivity PIPD-reinforced graphene fiber had a breaking elongation of 10%, an ultimate tensile strength of 300 MPa, and a fracture toughness of 30 MJ / m 3 , the conductivity is 5×105 S·m -1 .
[0079] Comparative Example 1
[0080] A method for preparing silk fibroin-reinforced graphene fiber is basically the same as that of Example 3, except that in step (3), the PIPD fiber is replaced by silk fibroin and the methanesulfonic acid is replaced by water.
[0081] The final silk fibroin-reinforced graphene fiber has an elongation at break of 0.6%, an ultimate tensile strength of 150 MPa, and a fracture toughness of 8 MJ / m 3 , the conductivity is 3×10 5 S·m -1 .
[0082] Comparing Example 3 with Comparative Example 1, it can be seen that the elongation at break, ultimate tensile strength and toughness of Comparative Example 1 are significantly reduced, because hydrogen bonds are formed between silk fibroin molecules (SF) and graphene oxide and there is a strong adhesion interaction between the two. Compared with the induced orientation of PIPD, SF will hinder the orderly orientation of graphene oxide sheets during the spinning orientation process. In addition, the hydrogen bonding force between SF and graphene oxide is weakened after the fiber is chemically reduced, so the mechanical properties are reduced.
[0083] Example 4
[0084] A method for preparing high-toughness and high-conductivity PIPD-enhanced graphene fiber, the specific preparation steps are as follows:
[0085] (1) Pretreatment of graphene oxide powder: stirring the graphene oxide powder in deionized water at 900 rpm for 72 h, ultrasonicating for 3 h during stirring, and then filtering with 400 mesh nylon cloth. After precooling at -18 °C for 24 h, freeze-drying for 36 h to obtain a few-layer graphene oxide powder.
[0086] The mass volume ratio of graphene oxide powder to deionized water is 1 g:30 ml;
[0087] (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 60 h, and ultrasonicating for 2.5 h during stirring to prepare a graphene oxide solution with a concentration of 1.5 wt%;
[0088] (3) PIPD fibers (diameter 30-100 μm, thermal decomposition temperature 530 °C, primary fiber tensile strength 1.2 GPa) were added to methanesulfonic acid and stirred for 48 h. Ultrasonic treatment was performed for 2.5 h during stirring to prepare a 0.5 wt% PIPD solution.
[0089] (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, using two coagulation baths to perform wet spinning, and drying in an oven at 50°C after spinning;
[0090] The content of PIPD in the spinning solution is 30 wt% of graphene oxide; the first coagulation bath is AlCl 3 / phosphoric acid aqueous solution, AlCl 3 The concentration is 5 wt%, and the phosphoric acid concentration is 15 wt%; the second coagulation bath is an ethanol / water mixed solution with a volume ratio of ethanol to water of 3:1; the inner diameter of the needle is 0.1 mm, and the spinning speed is 15 mm·min -1 , the collection rate is 15 mm·min -1 ;
[0091] (5) The fibers spun in step (4) were chemically reduced at 80 °C for 18 h using 20 mL of a 1:2 hydroiodic acid / ethanol mixture, and then vacuum dried at 60 °C for 42 h to obtain high-toughness and high-conductivity PIPD-reinforced graphene fibers; the hydroiodic acid was a 45% by mass aqueous solution of hydrogen iodide.
[0092] The resulting high-toughness and high-conductivity PIPD-reinforced graphene fiber has an elongation at break of 18%, an ultimate tensile strength of 1500 MPa, and a fracture toughness of 50 MJ / m 3 , the conductivity is 10 3 S·m -1 .
[0093] Example 5
[0094] A method for preparing high-toughness and high-conductivity PIPD-enhanced graphene fiber, the specific preparation steps are as follows:
[0095] (1) Pretreatment of graphene oxide powder: stirring the graphene oxide powder in deionized water at a speed of 1000 rpm for 96 h, ultrasonicating for 3 h during stirring, and then filtering with a 600-mesh nylon cloth. After precooling at -18 °C for 24 h, freeze-drying for 48 h to obtain a few-layer graphene oxide powder.
[0096] The mass volume ratio of graphene oxide powder to deionized water is 1 g:40 ml;
[0097] (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 72 h, and ultrasonicating for 3 h during the stirring process to prepare a graphene oxide solution with a concentration of 22 wt%;
[0098] (3) PIPD fibers (diameter 30-100 μm, thermal decomposition temperature 530 °C, primary fiber tensile strength 1.2 GPa) were added to methanesulfonic acid and stirred for 72 h. Ultrasonication was performed for 3 h during stirring to prepare a PIPD solution with a concentration of 1 wt%;
[0099] (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, using two coagulation baths to perform wet spinning, and drying in an oven at 60°C after spinning;
[0100] The content of PIPD in the spinning solution is 50 wt% of graphene oxide; the first coagulation bath is CrCl 3 / Phosphoric acid aqueous solution, CrCl 3 The concentration is 5 wt%, and the phosphoric acid concentration is 20 wt%; the second coagulation bath is an ethanol / water mixed solution with a volume ratio of ethanol to water of 3:1; the inner diameter of the needle is 0.1 mm, and the spinning speed is 20 mm min -1 , the collection rate is 20 mm·min -1 ;
[0101] (5) The fibers spun in step (4) were chemically reduced at 90 °C for 12 h using 20 mL of a 1:3 volume ratio of hydroiodic acid / ethanol mixture, and then vacuum dried at 80 °C for 48 h to obtain high-toughness and high-conductivity PIPD-reinforced graphene fibers; the hydroiodic acid was a 45% by mass aqueous solution of hydrogen iodide.
[0102] The final high-toughness and high-conductivity PIPD-reinforced graphene fibers (50%PIPD / GOFs) have an elongation at break of 20%, an ultimate tensile strength of 1200 MPa, and a fracture toughness of 70.2 MJ / m 3 , conductivity is 100 S·m -1 .
[0103] Example 6
[0104] A method for preparing high-toughness and high-conductivity PIPD-reinforced graphene fiber is basically the same as Example 5, except that the content of PIPD in the spinning solution in step (4) is 7.5 wt% of the graphene oxide.
[0105] The final high-toughness and high-conductivity PIPD-reinforced graphene fiber (7.5%PIPD / GOFs) has a breaking elongation of 13%, an ultimate tensile strength of 500MPa, and a fracture toughness of 35MJ / m 3 , the conductivity is 5×10 4 S·m -1 .
[0106] like Figure 1 As shown in the XRD data, the =7.0° and 26.67° diffraction peaks correspond to (001) and (200) crystal planes, respectively. The (001) crystal plane with a crystal plane spacing of d ≈ 12.62 Å is a layered stacking structure between PIPD molecular chains, while the (001) crystal plane with d ≈ 3.35 Å is a short-range ordered structure within the PIPD molecule, and the interlayer spacing of d ≈ 10.21 Å is the ordered stacking interlayer spacing of GO sheets. XRD data show that there is a dual-phase crystal structure in PIPD / GOFs.
Claims
1. A method for preparing high-toughness and high-conductivity PIPD-enhanced graphene fiber, characterized in that: The graphene oxide solution and the PIPD solution are mixed to prepare a spinning solution, two coagulation baths are used for wet spinning, and after spinning, chemical reduction and vacuum drying are performed in sequence to obtain PIPD-reinforced graphene fibers with high toughness and high conductivity; The solvents of graphene oxide solution and PIPD solution were both methanesulfonic acid; The content of PIPD in the spinning solution is 0.1~50wt% of graphene oxide; The first coagulation bath is a metal ion / phosphoric acid aqueous solution, and the second coagulation bath is an ethanol / water mixed solution; In the first coagulation bath, the metal ion concentration is 2-5 wt%, and the phosphoric acid concentration is 2-20 wt%. In the second coagulation bath, the mass percentage of ethanol relative to water is 60-90%. The metal ion is Ca 2+ Mg 2+ 、Co 2+ , Fe 3+ 、Al 3+ or Cr 3+ ; The high-toughness and high-conductivity PIPD-reinforced graphene fibers have an elongation at break of 2-20%, an ultimate tensile strength of 250-1500 MPa, and a fracture toughness of 10-70 MJ / m 3 , the conductivity is 10 2 ~10 6 S·m -1 .
2. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 1, characterized in that: The content of PIPD in the spinning solution is 0.1~1wt% of graphene oxide. The elongation at break of the high-toughness and high-conductivity PIPD-reinforced graphene fiber is 2~10%, and the fracture toughness is 10~30 MJ / m 3 , the conductivity is 5×10 5 ~10 6 S·m -1 .
3. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 1, characterized in that: The content of PIPD in the spinning solution is 1~15wt% of graphene oxide. The elongation at break of the high-toughness and high-conductivity PIPD-enhanced graphene fiber is 5~15%, and the fracture toughness is 30~40 MJ / m 3 , the conductivity is 10 4 ~5×10 5 S·m -1 .
4. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 1, characterized in that: The content of PIPD in the spinning solution is 15-30wt% of graphene oxide. The elongation at break of the high-toughness and high-conductivity PIPD-reinforced graphene fiber is 15-18%, and the fracture toughness is 40-50 MJ / m 3 , the conductivity is 10 3 ~10 4 S·m -1 .
5. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 1, characterized in that: The content of PIPD in the spinning solution is 30~50wt% of graphene oxide. The elongation at break of the high-toughness and high-conductivity PIPD-enhanced graphene fiber is 18~20%, and the fracture toughness is 50~70 MJ / m 3 , the conductivity is 10 2 ~10 3 S·m -1 .
6. A method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to any one of claims 1 to 5, characterized in that: The specific preparation steps are as follows: (1) Pre-treating graphene oxide powder: dispersing the graphene oxide powder in deionized water, filtering and freeze-drying; (2) adding the pretreated graphene oxide powder to methanesulfonic acid, stirring for 24 to 72 h, and ultrasonicating for 1 to 3 h during the stirring process to prepare a graphene oxide solution with a concentration of 0.1 to 2 wt%; (3) Add PIPD fiber to methanesulfonic acid and stir for 24 to 72 h. Ultrasonicate for 1 to 3 h during stirring to prepare a PIPD solution with a concentration of 0.1 to 1 wt%; (4) mixing the graphene oxide solution in step (2) with the PIPD solution in step (3), stirring and ultrasonicating to obtain a spinning solution, and performing wet spinning; (5) The fibers spun in step (4) are chemically reduced and then vacuum dried to obtain high-toughness and high-conductivity PIPD-reinforced graphene fibers.
7. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 6, characterized in that: In step (1), the graphene oxide powder is dispersed in deionized water, specifically, the graphene oxide powder is stirred in the deionized water for 48 to 96 hours, and ultrasonic treatment is performed for 2 to 3 hours during the stirring process; Use 300~600 mesh nylon cloth for filtration.
8. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 6, characterized in that: The spinning speed in step (4) is 5-20 mm·min -1 , the collection rate is 5~20 mm·min -1 After spinning, it is placed in an oven at 40~60 ℃ to dry.
9. The method for preparing a high-toughness and high-conductivity PIPD-enhanced graphene fiber according to claim 6, characterized in that: The reducing agent used for the chemical reduction in step (5) is a hydroiodic acid / ethanol mixture, the volume ratio of hydroiodic acid to ethanol is 1:0.1-3, and the hydroiodic acid is a 45% by mass hydrogen iodide aqueous solution.
Citation Information
Patent Citations
A kind of high-orientation graphene oxide fiber and preparation method thereof
CN115341307B
Preparation method of high-performance graphene fiber
CN115449922A
High-strength graphene fiber and preparation method thereof
CN115522385A
Chitosan modified boron nitride and graphene fiber composite material as well as preparation method and application thereof
CN116199940A
Graphene fiber bundle and preparation method thereof
CN117568953A